Stroke prevention in atrial fibrillation - Hobbs, F (2003)
This article explores the strengths and weaknesses of current treatment pathways of atrial fibrillation as discussed at a multidisciplinary meeting of healthcare professionals organised by the Thrombosis Quorum. By discussing case studies using a Socratic method of dialogue to elicit better questioning of management practices, the meeting reached a consensus on various issues in the care of the patient with atrial fibrillation.